2023
DOI: 10.6018/rcsar.451151
|View full text |Cite
|
Sign up to set email alerts
|

Developing teamwork skills in accounting students: is communication apprehension a potential barrier?

Abstract: Although research and pronouncements have identified the increased relevance of ‘soft’ skills for future professionals in accounting, graduates continue to exhibit deficiencies in those skills. Employers and practitioners emphasize that the dynamic business environment requires more than just technical knowledge; excellent teamwork, communication and analytical skills are also of paramount importance. Despite numerous attempts to improve teamwork skills there is evidence that the responses to the acknowledged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…These considerations are strengthened by studies that support the presence of values on a scale between =0.70 and =0.95. 58 The principal components analysis using the varimax rotation method to explore the factorial structure of the teachers’ academic knowledge scale was based on the criterion (eigenvalue>1). 59 From the 7 initial indicators the procedure of reduction.…”
Section: Discussionmentioning
confidence: 99%
“…These considerations are strengthened by studies that support the presence of values on a scale between =0.70 and =0.95. 58 The principal components analysis using the varimax rotation method to explore the factorial structure of the teachers’ academic knowledge scale was based on the criterion (eigenvalue>1). 59 From the 7 initial indicators the procedure of reduction.…”
Section: Discussionmentioning
confidence: 99%
“…According to Rua and Maia (2023), employers should use various creative techniques to improve soft skills, especially negotiation and problem solving. According to Arquero et al (2023) communication barriers have a negative relationship with group work self-efficacy, and therefore educators should develop both teamwork and communication skills in students and thus reduce communication concerns. Haidar (2022) conducted a perception analysis of soft skills and distance education and found that distance education has a positive effect on the development of soft skills.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While soft skills come from his attitudes and behavior Cernușca (2020). According to Arquero et al (2023) the development of interpersonal and communication skills is the most important for graduates. According to this study, soft skills (mainly communication and teamwork) are much more important than hard skills.…”
Section: Introductionmentioning
confidence: 99%